Honeycomb defects works / Muhammad Hafiz Abdullah - Abdullah, Muhammad Hafiz (Universiti Teknologi MARA, Perak, 2019)
Structure defects is one of the major components of building problems that significantly needed attention. When a building fails to function as it should, we must immediately seek for the determination. Structure defects occurs to either the new building or the old ones. The example of the building defects is defective honeycomb of walls and slab in building. This report was conducted for the defective honeycomb of wall and slab at Level 18 to Level 28 Block B at Riana Dutamas, Segambut, Kuala Lumpur site. The objectives of this report are to identify the type of defective honeycomb of walls and slabs in buildings, to know the exact sequence of work for defective honeycomb and to identify the problem and solution for defective honeycomb of walls and slabs in buildings.